A new Mylia Gray (Myliaceae, Hepaticae) species from North Vietnam extends the range of the genus to the Paleotropics - Bakalin, Vadim; Vilnet, Anna (Phytotaxa, 2018)
The range of the genus Mylia is extended to South-East Asia with the description of Mylia vietnamica Bakalin et Vilnet sp. nov. This species, the southernmost representative of the genus, was recently discovered in North Vietnam. The new species superficially resembles M. taylorii (Hook.) Gray, but differs from the latter in its transversely elliptic leaves that are crispate along the margin, the peculiar shape of its trigones (large, but angularly concave in the new species), and its stem cross section. Molecular evidence is presented that confirms the new species is genetically distinct from the other East Asian representatives of the genus. Mylia vietnamica could also occur in the adjacent mountainous areas of northern Laos and southern Yunnan (China). Reports of M. taylorii for the latter province may actually belong to M. vietnamica.